The Analysis of Cultural Content The Eight Grade Junior High School Students English Textbook - Budianto, Faradiba; Pradana, Dian Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The aims of this research are to analyze the culture categories and get the most dominant category presented in the textbook. Qualitative research design, specifically content analysis of textbooks is employed in the study. This research use data analysis according to Miles and Huberman (1992) explain that analysis involves three concurrent activities: data reduction, data display, and conclusion drawing/verification. The primary data source for this study is the researcher employs established categories to analyze the data, including food and drink, locations, art, ceremonies, social behavior, beliefs and values, history, and individuals. These categories were developed by Adoskou, Moran, Dweik, and Al-Sayed in 1990, 2001, and 2015. The textual and visual data are examined based on the cultural categories of source culture, target culture, and worldwide culture. These categories were developed by Cortazzi & Jin in 2022.